Laminin-511 Supplementation Enhances Stem Cell Localization With Suppression in the Decline of Cardiac Function in Acute Infarct Rats. Issue 5 (May 2019) - Sougawa, Nagako; Miyagawa, Shigeru; Fukushima, Satsuki; Yokoyama, Junya; Kitahara, Mutsunori; Harada, Akima; Mochizuki-Oda, Noriko; Sato-Nishiuchi, Ryoko; Sekiguchi, Kiyotoshi; Sawa, Yoshiki
Abstract : Background: The extracellular matrix, in particular basement membrane components such as laminins (LMs), is essential for stem cell differentiation and self-renewal. LM511 and LM221 are the main extracellular matrix components of the epicardium, where stem cells were abundant. Here, we examined whether LMs affected the regeneration process by modulating stem cell activities. Methods: In vitro, adhesive, and proliferative activities of mesenchymal stem cells (MSCs) were evaluated on LM511 and LM221. To examine the effects of LMs in vivo, we established an acute myocardial infarction model by ligation of the proximal part of the left anterior descending artery at the height of the left atrial appendage and then placed atelocollagen sheets with or without LM511 and LM221 over the anterolateral surface of the left ventricular wall. Four or 8 weeks later, cardiac function, histology, and cytokine expressions were analyzed. Results: MSCs showed greater proliferation and adhesive properties on LM511 than on LM221. In vivo, at 4 weeks, isolectin B4–positive cells were significantly higher in the LM511-transplanted group than in the control group. Moreover, some isolectin B4–positive cells expressed both platelet-derived growth factor receptor α and CD90, suggesting that LM511 enhanced MSC recruitment and attachment at the implanted site. After 8 weeks, these cells were more abundant than at 4 weeks. Transplantation with LM511-conjugated sheets increased the expression of cardioprotective and angiogenic factors. Conclusions: Transplantation with LM511-conjugated sheets enhanced MSC localization to the implantation site and modulated stem cells activities, leading to angiogenesis in acute myocardial infarction rat models.